Association of sleep disturbances with diminished ovarian reserve in women undergoing infertility treatment - Xue-Fen Cai; Bi-Ying Wang; Jian-Ming Zhao; Mei-Xin Nian; Qi-Chang Lin; Jie-Feng Huang (Scientific Reports)
Abstract With an aging population seeking infertility treatment, diminished ovarian reserve (DOR) is a prevalent indication for assisted reproductive technology (ART). This study aims to investigate the relationship between sleep parameters and DOR among women attending an infertility clinic. Methods We consecutively enrolled women attending an infertility clinic from July 2020 to June 2021. Participants completed the Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale(ESS), and STOP-Bang Questionnaire to assess self-reported sleep quality. DOR-related indices including antral follicle count, anti-Müllerian hormone(AMH), follicle-stimulating hormone (FSH) were evaluated. A total of 979 women were enrolled, with 148 classified into the DOR group and 831 in the non-DOR group. The DOR group was notably older compared to the non-DOR group. Analysis showed that the DOR group exhibited significantly shorter sleep onset latency (p = 0.001) and shorter total sleep duration (p = 0.014) compared to the non-DOR group. Logistic regression analysis identified age, PSQI-sleep latency, and PSQI score as independent factors associated with an increased risk of DOR(all p < 0.05). Furthermore, stratified analysis by age group revealed that snoring and PSQI-sleep latency were particularly notable risk factors for DOR among women aged 35 years and older (OR = 2.489, p = 0.040; OR = 2.007, p = 0.008, respectively). Our study highlights that shorter sleep onset latency and shorter total sleep duration may be associated with DOR among women undergoing ART treatments. Particularly noteworthy, snoring and sleep latency were identified as additional risk factors for DOR among women aged 35 years and older.